Ehzele Laimbwe and Water Rituals in the North West Region of Cameroon - Kah, Henry Kam (Matrix)

(untitled) (International Network for Training, Education, and Research on Culture, 2025)
Water rituals are part of daily life in Cameroon’s Western Grassfields in general and Laimbweland in particular. Women are connected with these rituals, which play an important role in fecundity and procreation, pacification of the living-dead, dissipation of malevolent spirits, witches and wizards, and treatment of ailments. In this article, I claim that water rituals of Ehzele Laimbwe (women) in North West Cameroon serve vital socio-cultural and cosmological purposes by preserving culture, forestalling looming disaster, and cleansing the community of subverting evil spirits. Regrettably, the advent of Christianity and Western education, among other external influences, diminished participation, with only a portion of the population continuing to subscribe to these rituals cultural practices of old. Rituals are performed during crab and tadpole fishing, for birth and death, at the start of the dry season, during masquerade performances at funerals, and when there is imminent calamity. Employing the methodology of critical observation, discussion, oral interviews and analyzing available documents, I surmise that Ehzele Laimbwe rituals in Baisso, Bu, and Mbengkas (Laimbwe villages) aptly serve these socio-cultural and cosmological purposes. The socio-cultural challenges that Laimbwe face today are due, in part, to their non-respect for and lack of participation in these rituals.